2014
DOI: 10.3389/fmars.2014.00013
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal variability in irradiance affects herbicide toxicity to the marine flagellate Dunaliella tertiolecta

Abstract: Photosynthetically Active Radiation (PAR) and Ultraviolet Radiation (UVR) of the solar spectrum affect microalgae directly and modify the toxicity of phytotoxic compounds present in water. As a consequence seasonal variable PAR and UVR levels are likely to modulate the toxic pressure of contaminants in the field. Therefore, the present study aimed to determine the toxicity of two model contaminants, the herbicides diuron and Irgarol ® 1051, under simulated irradiance conditions mimicking different seasons. Irr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 39 publications
1
3
0
Order By: Relevance
“…The strong synergistic effects on growth when algae were exposed to high diuron concentrations and the low-light levels were consistent with earlier hypotheses of synergistic interactions as the stressor magnitudes intensify [11], and are consistent with literature findings that reported a lower toxic response when marine microalgae were exposed to a mixture of PSII-inhibiting herbicides in lower light conditions, compared to higher light conditions [56]. Growth inhibition of microalgae is influenced by multiple underlying physiological responses.…”
Section: Discussionsupporting
confidence: 90%
“…The strong synergistic effects on growth when algae were exposed to high diuron concentrations and the low-light levels were consistent with earlier hypotheses of synergistic interactions as the stressor magnitudes intensify [11], and are consistent with literature findings that reported a lower toxic response when marine microalgae were exposed to a mixture of PSII-inhibiting herbicides in lower light conditions, compared to higher light conditions [56]. Growth inhibition of microalgae is influenced by multiple underlying physiological responses.…”
Section: Discussionsupporting
confidence: 90%
“…In situ, this means that an individual plant in full sunlight might be nearly unaffected, while another plant of the same species in the shade might be affected to a much greater extent by a single herbicide with a photosynthesis II inhibition mode of action (Snel et al 1998). Also, Sjollema et al (2014) showed that the toxicity of diuron and irgarol to the marine flagellate was higher under simulated spring irradiance than under autumn irradiance, which indicates that herbicide toxicity in the field is also seasonally variable. This clearly shows that the sensitivity of aquatic primary producers to herbicides is also depending on their metabolic activity, hence the strict set of standardized test conditions used in regulatory assessment of herbicides.…”
Section: Sensitivity Of Freshwater Primary Producers To Herbicidesmentioning
confidence: 99%
“…Binary mixtures of herbicides (diuron, tebuthiuron, atrazine, simazine and hexazinone) exhibited additive toxicity to the microalgae Navicula sp., Cylindrotheca closterium, Nephroselmis pyriformis and Phaeodactylum tricornutum (Magnusson et al 2010). Sjollema et al (2014) tested the effect of an equitoxic mixture of the herbicides irgarol and diuron on photosynthesis of Dunaliella tertiolecta. Although the mode of action of both herbicides was inhibition of photosynthesis, a more than additive effect of the herbicides in the mixture was observed.…”
Section: Mixture Toxicity Of Herbicides To Aquatic Primary Producersmentioning
confidence: 99%
See 1 more Smart Citation